2021
DOI: 10.1177/08944865211012139
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Foundations of Management in Family Firms: Emotions, Memories, and Experiences

Abstract: Exploring the psychological foundations of management in family firms is necessary to understand why they formulate and implement strategies differently from nonfamily firms, and why and how family firm behavior varies across different family firms. Picone et al. (2021. The psychological foundations of management in family firms: Values, biases, and heuristics. Family Business Review, 34(1), 12-32) have proposed a conceptual framework for the psychological foundations of management in family business, examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Previous studies have found that perceived injustice produces negative emotions that trigger conflict, especially between siblings, and during critical events such as ownership transfer, succession, and pay dispersion (Avloniti et al, 2014 ; Ensley et al, 2007 ). Our study, in line with Picone et al ( 2021 ) and Humphrey et al ( 2021 ), highlights that managing emotions is a driver to ensure family firm's success, and pruning appears to be a helpful tool to manage emotions, and conflicts between family members, mainly when derived from conflicts of interest between active and passive siblings and/or family members.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have found that perceived injustice produces negative emotions that trigger conflict, especially between siblings, and during critical events such as ownership transfer, succession, and pay dispersion (Avloniti et al, 2014 ; Ensley et al, 2007 ). Our study, in line with Picone et al ( 2021 ) and Humphrey et al ( 2021 ), highlights that managing emotions is a driver to ensure family firm's success, and pruning appears to be a helpful tool to manage emotions, and conflicts between family members, mainly when derived from conflicts of interest between active and passive siblings and/or family members.…”
Section: Discussionsupporting
confidence: 88%
“…Second, we see a need to better understand the implication of the demographics of FF members on the CSR behavior and performance of their firms. Here, we even encourage future scholars to draw on the psychological foundations of management in family firms (Humphrey et al, 2021;Picone et al, 2021) to understand how the heuristics, biases, values, emotions, experiences, and memories of different family and non-family actors within the FF may affect CSR strategies and behaviors. Third, although ownership criteria have been the most adopted in the empirical literature to distinguish FFs from their non-family counterparts (De Massis et al, 2012), our knowledge of the impact of ownership factors, Category 5: Outcomes of CSR Q5.1) What is the relationship between firm CSR adoption and firm performance, including environmental and financial performance?…”
Section: Limitations and Research Agendamentioning
confidence: 99%
“…As such, the cognitive and psychological characteristics of decision-makers have been recognized as crucial (Domurath et al, 2020) to understand how organizations seek, recognize, and exploit opportunities through novel resource combinations (Stoian et al, 2018;Zahra et al, 2005). These aspects are particularly relevant for family multinationals, since family firms are recognized for their psychological, behavioral, social and cognitive uniqueness likely to lead to idiosyncratic entrepreneurial decisions and behaviors (Nason et al, 2019;Picone et al, 2021, Humphrey et al, 2021. However, our review shows that studies tend to combine internationalization scale and scope (Alayo et al, 2019), or mix exports and FDIs (Cesinger et al, 2016;Singla et al, 2014), limiting our understanding of the entrepreneurial underpinnings of family multinationals as family firms that internationalize beyond exports.…”
Section: Family Multinationalsmentioning
confidence: 99%